(untitled) (Iranian Journal of Kidney Diseases, 2010)
Hypomagnesemia is defined as a serum magnesium level less than 1.8 mg/dL (< 0.74 mmol/L). Hypomagnesemia may result from inadequate magnesium intake, increased gastrointestinal or renal losses, or redistribution from extracellular to intracellular space. Increased renal magnesium loss can result from genetic or acquired renal disorders. Most patients with hypomagnesemia are asymptomatic and symptoms usually do not arise until the serum magnesium concentration falls below 1.2 mg/dL. One of the most life-threatening effects of hypomagnesemia is ventricular arrhythmia. The first step to determine the likely cause of the hypomagnesemia is to measure fractional excretion of magnesium and urinary calcium-creatinine ratio. The renal response to magnesium deficiency due to increased gastrointestinal loss is to lower fractional excretion of magnesium to less than 2%. A fractional excretion above 2% in a subject with normal kidney function indicates renal magnesium wasting. Barter syndrome and loop diuretics which inhibit sodium chloride transport in the ascending loop of Henle are associated with hypokalemia, metabolic alkalosis, renal magnesium wasting, hypomagnesemia, and hypercalciuria. Gitelman syndrome and thiazide diuretics which inhibit sodium chloride cotransporter in the distal convoluted tubule are associated with hypokalemia, metabolic alkalosis, renal magnesium wasting, hypomagnesemia, and hypocalciuria. Familial renal magnesium wasting is associated with hypercalciuria, nephrocalcinosis, and nephrolithiasis. Asymptomatic patients should be treated with oral magnesium supplements. Parenteral magnesium should be reserved for symptomatic patients with severe magnesium deficiency (< 1.2 mg/dL). Establishment of adequate renal function is required before administering any magnesium supplementation.